Larval stages of Stenocionops furcatus (Olivier, 1791) (Decapoda : Brachyura : Majoidea) and a reappraisal of larval morphological characters for Mithracidae - Santana, W.; Marques, F.; Pohle, G. (Oxford University Press, 2004)
Stenocionops furcatus is a spider crab found in the western Atlantic, from Georgia, USA to Rio Grande do Sul, Brazil, on sand, coral, rocks or mud bottoms from the intertidal zone to 180 m. We describe all laboratory-reared larval stages of S. furcatus obtained from the northern coast of São Paulo State, Brazil, and compare our data with existing larval descriptions for the genus and other mithracids. The larval development of S. furcatus consists of two zoeal stages and one megalopa. The durations of the first and second zoeal stage were similar to4 and 5 days respectively, the megalopa appearing 10-18 days after hatching. Our results show that the zoeae of S. furcatus differ from those of other Mithracidae by possessing four setae on the proximal lobe of the coxal endite of the maxilla, instead of five, and by the presence of mid-dorsal setae on the third abdominal somite in the second zoeal stage, which are lacking in other mithracids. Larval descriptions for Stenocionops in two previous publications were attributed to the subspecies S. furcatus coelatus from the Caribbean. Larvae from Brazilian waters closely resemble one of these accounts, suggesting that this taxon extends beyond the West Indies and that the other description represents larvae of S. furcatus furcatus. Additional morphological details, not available previously, are provided.